2020
DOI: 10.1101/2020.11.10.376491
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temporal patterning of the central nervous system by a shared transcription factor code

Abstract: The molecular mechanisms that ensure the reproducible generation of neuronal diversity in the vertebrate nervous system are incompletely understood. Here we provide evidence of a temporal patterning program consisting of cohorts of transcription factors expressed in neurons generated at successive developmental timepoints. This program acts in parallel to spatial patterning, diversifying neurons throughout the nervous system and in neurons differentiated in-vitro from stem cells. We demonstrate the TGFβ signal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 111 publications
(208 reference statements)
2
23
0
Order By: Relevance
“…In the olfactory epithelium, they are involved in the correct specification of late born olfactory receptors (Bashkirova et al, 2020). They are required for the correct specification of late born neuron types in various other regions including the dorsal spinal cord (Sagner et al, 2020). And, they have been shown to accelerate glial competency in human included pluripotent stem cells (Tchieu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the olfactory epithelium, they are involved in the correct specification of late born olfactory receptors (Bashkirova et al, 2020). They are required for the correct specification of late born neuron types in various other regions including the dorsal spinal cord (Sagner et al, 2020). And, they have been shown to accelerate glial competency in human included pluripotent stem cells (Tchieu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many CREs show temporally dynamic activity patterns that are shared between germinal zones (Fig. 4D), arguing for a mode of cell fate induction through shared temporal cues ( 4 , 9 , 57 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although we found that the dynamics of CRE activity and conservation across development can mostly be explained by cellular differentiation and maturation, additional temporal differences could be present, even between cells at the same differentiation state. Such differences could arise from intrinsic temporal patterning cues, as recently described in the context of cell fate specification ( 57 , 68 ), as well as extrinsic factors, such as changes in the availability of a morphogen or a ligand, synaptic simulation and interactions with neighboring cells ( 16 ). To assess the contribution of such temporal signals we focused on GCs, because these cells have a protracted differentiation trajectory (E13-P14) and do not have distinct temporally-specified subtypes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sharp segregation of progenitor domains in the developing spinal cord has long suggested that spatial patterning is a key driver of neuronal diversity in the central nervous system (CNS). However, temporal patterning was recently proposed to be also at play and to involve the same gene networks throughout the CNS (Sagner et al, 2020). In the neocortex, the graded expression of patterning genes, the sequential production of deep and upper layers neurons and the changes in the transcriptomic signature associated with AP maturation (Okamoto et al, 2016; Telley et al, 2019) clearly point to the importance of temporal mechanisms.…”
Section: Discussionmentioning
confidence: 99%